Progress in the clinical treatment of keloids - Qi, Wenli; Xiao, Xinyue; Tong, Jing; Guo, Nengqiang (Frontiers in Medicine, 2023)
Keloid is a pathological scar that is higher than the skin surface following skin damage. Its lesion range often extends beyond the original damage boundary and does not naturally subside over time. Its pathogenesis is very complex, currently the main causes include fibroblast excessive proliferation, collagen and extracellular matrix (Extracellular matrix, ECM) excessive deposition, excessive angiogenesis, and so on. The traditional treatment method primarily involves surgical intervention, but it is associated with a high recurrence rate post-surgery. Consequently, many treatment methods are derived according to the different clinical characteristics of keloid. This paper will review the therapeutic progress in recent years from surgical treatment, physiotherapy, drug therapy, and biological therapy, with the goal of offering valuable insights for the clinical treatment of keloids.